Una revisión sobre el concepto de competencia educativa (2017)
The document adress the differents aspects related with “competence” concept, which is the articulating axis around which the different training programs in higher education are structured, and particularly in Public Accounting. This reflection reflects the difficulty in understanding the term, and the inconsistency of their use in the design of different accounting curricula. This work concludes that is fundamental to broaden the debate about the concept, in an environment that is related with the capabilities and labour performances of the future accountants.